15. RELIABILITY AND VALIDITY OF THE VIETNAMESE PEDIATRIC SLEEP QUESTIONNAIRE (PSQ) (Vietnam Journal of Community Medicine, 2023)
Objectives: Determining the reliability and validity of the Vietnamese version of the PSQ questionnaire.Methods:Study subjects: Children aged 3-17 years admitted to respiratory clinics in University Medical Center and CHAC Clinic 1, Ho Chi Minh City, from November 2020 to June 2021, were included. Study design: A prospective cross-sectional study. Subjects were interviewed using PSQ questionnaire and performed type III polysomnography for comparison. Results: The V-PSQ had the I-CVI for all questions scored 1.00 and the impact score of each question > 1.5. Internal consistency: Cronbach’s alpha coefficient for the whole questionnaire was 0.866, the snoring domain 0.736, the sleep domain 0.682, behavioral domain 0.782. Test-retest reliability: Spearman correlation coefficient 0.823 for the entire questionnaire (p < 0.01), Snoring domain 0.813, Sleep domain 0.875, Behavioral domain 0.77. There was no correlation between the V-PSQ questionnaire and the apnea-hypopnea index. Conclusion: The V-PSQ questionnaire can potentially screen OSA in children. However, more studies with larger sample sizes are needed.
Keywords: Obstructive sleep apnea syndrome, children, screening questionnaire, polysomnography.